Spain : Financial Sector Assessment Program-Technical Note-Interconnectedness and Spillover Analysis in Spain's Financial System. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note discusses the findings of the Financial Sector Assessment Program about interconnectedness and spillover in Spain's financial system. Financial intermediaries in Spain are interconnected through conglomerate ownership, common exposures, and inter-sectoral claims. The main source of cross-sectoral connectedness appears to be insurance companies' exposures to banks, while exposures of banks to insurers or to mutual funds appear limited at present. Empirical analysis using both exposure and market data suggest strong cross-border interconnectedness. Contagion within the domestic interbank market appears to be limited at present. There are also strong cross-sectoral linkages between banks and other parts of the financial system in Spain, but systemic risks from those linkages appear to be limited.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet